Measurement of multi-red blood cells interactions in blood flow by confocal micro-PTV - Lima, R. (2010)
In microcirculation the flow behavior of red blood cells (RBCs) plays a crucial role in many physiological and pathological phenomena. For instance, the interaction of RBCs in shear flow is believed to play an important role to the thrombogenesis process. Despite the relevance of this phenomenon on the blood mass transport, very little studies have been performed during the years, partly due to the absence of adequate visualization techniques able to obtain both direct and quantitative measurements on multi-RBCs motions in concentrated suspensions. Past studies on both individual and concentrated RBCs used conventional microscopes and/or ghost cells to obtain visible trace RBCs at high concentration suspension of blood cells [1, 2]. Recently, advances of confocal microscopy and consequent advantages over conventional microscopes have led to an emerging technique known as confocal micro-PIV [3, 4]. This paper presents the application of a confocal micro- PTV system to measure RBC-RBC hydrodynamic interactions in flowing blood.